Resolving apparent conflicts between theoretical and experimental models of phosphate monoester hydrolysis - Duarte, F; Åqvist, J; Williams, N; Kamerlin, S (American Chemical Society, 2014)
Understanding phosphoryl and sulfuryl transfer is central to many biochemical processes. However, despite decades of experimental and computational studies, a consensus concerning the precise mechanistic details of these reactions has yet to be reached. In this work we perform a detailed comparative theoretical study of the hydrolysis of p-nitrophenyl phosphate, methyl phosphate and p-nitrophenyl sulfate, all of which have served as key model systems for understanding phosphoryl and sulfuryl transfer reactions, respectively. We demonstrate the existence of energetically similar but mechanistically distinct possibilities for phosphate monoester hydrolysis. The calculated kinetic isotope effects for p-nitrophenyl phosphate provide a means to discriminate between substrate- and solvent-assisted pathways of phosphate monoester hydrolysis, and show that the solvent-assisted pathway dominates in solution. This preferred mechanism for p-nitrophenyl phosphate hydrolysis is difficult to find computationally due to the limitations of compressing multiple bonding changes onto a 2-dimensional energy surface. This problem is compounded by the need to include implicit solvation to at least microsolvate the system and stabilize the highly charged species. In contrast, methyl phosphate hydrolysis shows a preference for a substrate-assisted mechanism. For p-nitrophenyl sulfate hydrolysis there is only one viable reaction pathway, which is similar to the solvent-assisted pathway for phosphate hydrolysis, and the substrate-assisted pathway is not accessible. Overall, our results provide a unifying mechanistic framework that is consistent with the experimentally measured kinetic isotope effects and reconciles the discrepancies between theoretical and experimental models for these biochemically ubiquitous classes of reaction.